Introduction to fluid mechanics - Fox, Robert W. (John Wiley & Sons, 2004)
"Fox, McDonald & Pritchard provide a balanced approach to fluid mechanics that arms students with a proven problem-solving methodology. Students will learn to adopt an orderly approach to solving problems."